Strategi Pengkaderan Muhammadiyah dalam Mengembangkan Sumber Daya Manusia untuk Madrasah Ibtidaiyah Muhammadiyah Smart School - Prihono, Budi; R. Agus Trihatmoko (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the cadre system of Muhammadiyah in Karanganyar Regency, specifically in fulfilling the human resource (HR) needs for the management of Madrasah Ibtidaiyah Muhammadiyah Smart School Jaten. The research uses a case study method with a qualitative approach, where data is collected through interviews, Focus Group Discussions (FGD), participatory observation, and documentation. The findings indicate that the cadre system in Karanganyar has produced cadres who align with Muhammadiyah's ideology; however, there are challenges related to the low participation of cadres and misalignment of understanding between the administrators and other related parties. The evaluation of the cadre system reveals the need for reforms in communication and more in-depth training regarding the responsibilities of the cadres. The cadre training program focuses on developing technical and managerial competencies relevant to the needs of primary education at MIM Smart School Jaten. The conclusion emphasizes the necessity of reforming the cadre management to ensure competent HR that is ready to face future challenges, especially in managing high-standard education. Keywords: Muhammadiyah Cadre System, Human Resources, Muhammadiyah Smart School Jaten